Manajemen Airway, Breathing, Circulation (ABC) dan Dampaknya terhadap Early Warning Score (EWS) dalam Layanan Gawat Darurat: Mengevaluasi Efektivitas Intervensi Fundamental dalam Meningkatkan Hasil Pasien dan Pengambilan Keputusan Klinis - Sumara, Retno (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: to determine the implementation of Airway, Breathing, and Circulation (ABC) management interventions and their impact on the Early Warning Score (EWS) in the Emergency Installation of the Haji Hospital, East Java Province. Methods: Quantitative research design: pretest experimental one group pretest and posttest design. The population was patients aged ≥13 years with ABC disorders. The sample size was 80 people, according to the inclusion and exclusion criteria, by taking non-probability sampling with the consecutive sampling technique. Statistical tests using the Wilcoxon test. Results: The results of the study using the Wilcoxon test obtained an Asymp.sig value (2-tailed) = 0.000 or ρ value ≤ 0.05, indicating that airway, breathing, and circulation (ABC) management has an impact on better changes in early warning score (EWS) Conclusion: EWS is a systematic process to evaluate and measure early risk used to take preventive measures in emergencies that aim to minimize poor prognosis in the body system. The Airways, Breathing, and Circulation (ABC) method can be done for handling emergency conditions Keywords: Early warning Score(EWS), Manajemen Airway, Breathing dan Circulation(ABC)